(untitled) (Journal of actual problems of jurisprudence, 2019)
In the article, in relation to the socio-economic sphere, ensuring working conditions, social protection of employees and on the resolution of individual labor disputes, the analysis of the legislation is given, the issues of theory and practice of dispute resolution at the level of legal entities are considered. The conditions of consideration of labor disputes in the order of judicial proceedings are considered separately. The conditions for the development of acts of the employer and other internal documents aimed at the implementation of legislative acts are analyzed. The subject of the study, also, are some of the issues associated with the creation of “Tatulatiru ortalygy” on the basis of the Memorandum signed 19.03.2018, the head of the Supreme Court and the President of the Federation of trade unions. All issues that are the subject of the study are based on the Constitution of the Republic of Kazakhstan, the Concept of legal policy of the Republic of Kazakhstan for 2010-2020 from August 24, 2009 № 858, TC RK and other legislative acts. On the subject of the study, the types of documents formed in the activities of the Conciliation Commission for the consideration of labor disputes, the stages and terms of their consideration are subjected to analysis. On the formation of documents studied the conditions of development of the nomenclature of cases, its value and application. Key word: the act of the employer, conciliation commission, labour relations, production environment, working conditions, collective agreement, employment contract, structural subdivision.